2016
DOI: 10.1037/apl0000036
|View full text |Cite
|
Sign up to set email alerts
|

Selection BIAS: Stereotypes and discrimination related to having a history of cancer.

Abstract: Although great strides have been made in increasing equality and inclusion in organizations, a number of stigmatized groups are overlooked by diversity initiatives, including people with a history of cancer. To examine the workplace experiences of these individuals in selection contexts, we conducted 3 complementary studies that assess the extent to which cancer is disclosed, the stereotypes associated with cancer in the workplace, and discrimination resulting from these stereotypes. In a pilot study, we surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 27 publications
0
44
4
1
Order By: Relevance
“…However, the prevalence of mental illness within the working adult population draws attention to the need for researchers and practitioners to understand the ways in which mental illness affects workplace experiences, interactions, and dynamics. Stereotype content has been shown to be related to treatment of employees from underrepresented groups (Martinez, White, Shapiro, & Hebl, ), and future research should consider how stereotypes of employees with mental illness influence workplace interactions and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of mental illness within the working adult population draws attention to the need for researchers and practitioners to understand the ways in which mental illness affects workplace experiences, interactions, and dynamics. Stereotype content has been shown to be related to treatment of employees from underrepresented groups (Martinez, White, Shapiro, & Hebl, ), and future research should consider how stereotypes of employees with mental illness influence workplace interactions and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To follow then are representative examples of invisible stigmas and the organizational effects of such stigma on individuals should they become known during the course of employment. Specifically, we focus on previous employment history, sexual orientation, marital status, religion, and mental illness as exemplars of invisible stigmas, while recognizing that there are other invisible characteristics that can stigmatize individuals should they become known (e.g., medical history; Martinez, White, Shapiro, & Hebl, ).…”
Section: A Novel Typology Of Stigma In Organizationsmentioning
confidence: 99%
“…5,6 Likewise, findings indicate that AYA survivors were less comfortable making cancer-related disclosures at work/school than when among friends, possibly because of fears of workplace/school discrimination. 4,6,12 Indeed, half the participants indicated that they sometimes choose not to disclose their cancer status at work/school to avoid being seen or treated differently (It is noteworthy, however, that participants only self-disclosed to a mean of 70.5% of friends/acquaintances; thus, 100% workplace/school self-disclosure should not be expected.).…”
Section: Discussionmentioning
confidence: 99%
“…When 192 cancer survivors were asked whether they would disclose their cancer history when applying for a new position, 43% indicated that they would in some situations but not others. 4 In another study, men who had been diagnosed with prostate cancer expressed reluctance to disclose their diagnosis to others but also an obligation to tell supervisors to explain absences from work. 5 Survivors in a qualitative study echoed the need to make disclosures when work-related absences were anticipated; these survivors noted, however, that they would be less likely to disclose at work if no health-related accommodations were needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation